Persepsi Peserta Didik Terhadap Kebijakan Penerimaan Peserta Didik Baru (PPDB) Provinsi DKI Jakarta Sistem Zonasi Dengan Seleksi Usia Di Sekolah Menengah Atas (SMA) Tahun 2020 - Septy Tripujianti; Hanny Purnamasari; Ani Nurdiani Azizah (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Education is one of the important components to build Human Resources. This research was conducted to describe the problems of the New Student Admission (PPDB) policy for SMA Zoning system with age selection in DKI Jakarta Province. This research was conducted in October 2020. This research focuses on students who take part in PPDB SMA 2020, especially those who are domiciled in DKI Jakarta. This study used qualitative research methods. However, due to the current COVID-19 pandemic, the research was not carried out directly in the field. Researchers made observations through news mass media and several literature studies as well as collected data from the DKI Jakarta Education Office and data from interviews conducted by asking questions via googleform then distributed to students who had the following criteria: (1) Domicile in DKI Jakarta (2) participated in PPDB High School Year 2020. Based on the results of the study, it can be concluded that the DKI Jakarta Disdik decision regarding the 2020 PPDB which stipulates age selection in the zoning pathway has not yet been implemented on target. Where the purpose of the decision is to create equal distribution of education for students who have a poor economic background. However, from the interviews, 10 out of 13 students did not agree with the decision. The reason is because age selection does not provide fairness to high achieving students and students with younger ages. So that this decision is considered not to prioritize student achievement and does not support competition between students in achieving achievement.Keywords: PPDB Zoning, Problematic